“Revisión comparativa de la producción con tres fuentes proteicas de origen animal y vegetal en feedlots” - Donoso Franco, Domenica Natasha (2023)
This investigative study focuses on comparatively reviewing the production of three animal protein sources such as meat and bone, feather and fish meals, proteins of vegetable origin such as soybean, sunflower and wheat were also analyzed, in order to analyze what each protein contributes in the feeding of bovines. This project details the environmental impact that the production of both proteins has had, where it resulted in that those of animal origin are very harmful to the environment, while the vegetables are considerably less polluting. When comparing other of the objectives that deal with feed conversion efficiency, it reflects that animal proteins are excellent in digestibility, however, when using them they cause damage to health and the environment. On the other hand, vegetable proteins should be provided in greater quantities to animals with the advantage that the ecosystem would not be affected. To carry out the research, all kinds of information was collected from various sources, including books, magazines and online resources, with topics related to environmental impact, and weight gain in reference to feed conversion efficiency, food safety, digestibility. Some of the methods to carry out this inquiry were: Historical-logical method that specializes in examining the sources of the matter through documentary and bibliographical review, other methods used are deductive-inductive, which enables accurate, comprehensive information, focused and detailed on the most relevant issues of this important project.